Characterization of time-varying magnetic fields and temperature of helium gas exit during a quench of a human magnetic resonance system. (24th June 2019) - Pace, Nicola; Ricci, Leonardo; Scotoni, Mario; Perinelli, Alessio; Jovicich, Jorge
Abstract: The quench of a human magnetic resonance imaging system is a critical event that may occur spontaneously, as an accident or purposely in response to an emergency. Although a magnet's quench presents its own risks, little experimental data is available in this respect. In this study, the programmed quench of a human MRI scanner was used to measure the induced time varying magnetic fields ( d B / d t ) inside the bore in order to evaluate cardiac stimulation risks during a quench. Additionally, we measured the exit temperature of the helium gas, to evaluate potential implications in quench pipe design. The maximum d B / d t was 360 mT s −1 at the center of the magnet, far below the cardiac stimulation threshold (20 T s −1 ). The helium exit temperature reached 35 K, perhaps implying further considerations about quench pipe designs. Replication of similar experiments on programmed quenches, specially in high-field MRI systems, will be useful to further characterize quench risks.